Sonographic Assessment of Carotid Artery Stenosis in Atherosclerotic Patients by Color Doppler Ultrasound : Determinants of Quality of Life - Raza, Muhammad Ahmad; Zafar, Farwa Seemab; Sabir, Muhammad; Altuf, Laamia; Sultan, Hajra; Mehak Gillani, Syeda Hafiza (Pakistan Journal of Health Sciences, 2023)
Mostly patients with neck pain, cold sweats, chest pain, high blood pressure and heart palpitations are assessed by sonography. Because major blood vessels supplying the brain and face through carotid arteries. Mostly, intima media thickness is one of the markers of atherosclerotic patient that is widely used. The aim of study is to find out stenosis with carotid arteries with the help of color Doppler scan. The data was included in literature review from several search engines. In this literature review, olny 20 articles were used for extraction of data related to topic statement. The current study looked sonographic assessment of carotid artery in atherosclerotic patients. It is concluded that Color Doppler ultrasound is a non-invasive and easier modality of choice for evaluating the patient with atherosclerosis, it helps in diagnosis of flow as well as prediction of carotid artery stenosis.